Swallow's dance - Orr, Wendy, 1953- (Pajama Press, 2019)
Leira is training to be a priestess, but after an earthquake on her island forces her and her family to flee to Crete, there is a volcanic eruption that destroys the island and a tsunami that throws Crete into chaos, as she and her mother struggle to survive.